1976
DOI: 10.1093/infdis/133.supplement_2.a199
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Human Exogenous Leukocyte Interferon in Cytomegalovirus Infections

Abstract: Human leukocyte interferon was injected into nine patients with cytomegalovirus infections; four of these patients were congenitally infected, and five had acquired infections. In three patients viruria was completely inhibited. In five patients viral excretion in the urine was only transiently inhibited. Viremia was not significantly suppressed. The lymphocyte response to phytohemagglutinin was suppressed in two patients.Cytomegalovirus (CMV) has been associated with long-term, chronic infections in humans an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Studies of the specific effects of IFN-like responses on the HCMV viral life cycle have produced conflicting results. For example, it has been reported that IFN treatment does little to inhibit the viral life cycle (53,54), while other reports indicate that IFNs are effective at the inhibition of HCMV replication (55,56). To add greater complexity to the potentially diverse role for IFN responses in HCMV infection, IFN-␥, when combined with tumor necrosis factor alpha (TNF-␣), was shown to produce an HCMV replicationpermissive macrophage that was resistant to future IFN-␥-induced cytokines (57).…”
mentioning
confidence: 99%
“…Studies of the specific effects of IFN-like responses on the HCMV viral life cycle have produced conflicting results. For example, it has been reported that IFN treatment does little to inhibit the viral life cycle (53,54), while other reports indicate that IFNs are effective at the inhibition of HCMV replication (55,56). To add greater complexity to the potentially diverse role for IFN responses in HCMV infection, IFN-␥, when combined with tumor necrosis factor alpha (TNF-␣), was shown to produce an HCMV replicationpermissive macrophage that was resistant to future IFN-␥-induced cytokines (57).…”
mentioning
confidence: 99%
“…Administration of massive interferon doses may also affect CMV excretion in the urine. Viruria was completely inhibited in three ofnine patients with congenital or acquired infection treated by Emodi et al (6), and in five patients, viruria was transiently suppressed. Viremia was not affected.…”
mentioning
confidence: 79%
“…IFN of all types reduces CMV early and late antigen induction in fibro blasts in vitro [our unpublished data]. When IFN has been administered in vivo to pa tients with acute CMV infections, the results have been variable [38][39][40][41], There are indica tions that it may be useful for prophylaxis, delaying CMV infection in renal or bone marrow transplant recipients [42]. Similarly, IFN diminished EBV excretion in renal transplant recipients when given prophylactically [43].…”
Section: Discussionmentioning
confidence: 99%